Profil Gaya Belajar Ditinjau Dari Tipe Kepribadian Disc - Sihai, Non; Romiaty, Romiaty; Feronika, Nopi; Sukarningsi, Susi (Jurnal Bimbingan dan Konseling Pandohop, 2024)
Learning style is an individual's special mindset in receiving, processing information and learning new skills. The purpose of this study was to determine the description of learning styles in terms of DISC personality type. The research methodology uses survey research and analyzes it. The results of the study showed that: (1) Dominance personality type has Visual learning style as much as 8%, Auditory 5% and Kinesthetic 10%; (2) Influence personality type has Visual learning style as much as 5%, Auditory 5% and Kinesthetic 8%; (3) Steadiness personality type has Visual learning style as much as 24%, Auditory 3% and Kinesthetic 21%; (4) Compliance personality type has Visual learning style as much as 3%, Auditory 0% and Kinesthetic 8%. The conclusion is that students of the Guidance and Counseling study program have a Steadiness personality type as many as 17 people out of 38 respondents with visual and kinesthetic learning styles. This means that they have a personality type that really likes the process, willing to persevere, loyalty and able to work together in teams. They find it easier to learn material visually and through hands-on practice.